HOTS-Based Wordwall Interactive Quiz Media in Science Learning Content to Improve Learning Outcomes of Fifth-Grade Elementary School Students - Tiarawati, Putu; I Made Citra Wibawa; Kade Sathya Gita Rismawan (Universitas Pendidikan Ganesha, 2025)
This study addresses the issue of the limited use of learning media, which affects students' low learning outcomes. The proposed solution is to develop interactive and innovative learning media. The study aims to design, analyze the validity, practicality, and effectiveness of the HOTS-based Wordwall Quiz interactive learning media. The research follows the R&D (Research and Development) model using qualitative and quantitative data analysis. Data collection methods include validity and practicality questionnaires and tests for product effectiveness. The effectiveness study involved 29 fifth-grade students using a one-group pretest-posttest design, analyzed with a correlated t-test. Results show a material validity index of 3.8 and a media validity index of 3.9, both classified as highly valid. The practicality index also falls under the highly practical category. The effectiveness test significantly improved students' IPAS learning outcomes after using the HOTS-based Wordwall Quiz. It is concluded that the interactive Wordwall Quiz meets feasibility standards and enhances learning outcomes. The study implies that using interactive HOTS-based Wordwall Quiz positively impacts the learning process, fosters active and creative learning, and optimizes students’ understanding.